2018
DOI: 10.13057/biodiv/d190121
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of aroids (Araceae) in Bogor Botanic Gardens, Indonesia: Collection, conservation and utilization

Abstract: Yuzammi. 2018. The diversity of aroids (Araceae) in Bogor Botanic Gardens, Indonesia: Collection, conservation and utilization. Biodiversitas 19: 140-152. Bogor Botanic Gardens is an ex-situ conservation centre, covering an area of 87 ha, with 12,376 plant specimens, collected from Indonesia and other tropical countries throughout the world. One of the richest collections in the Gardens comprises members of the aroid family (Araceae). The aroids are planted in several garden beds as well as in the nursery. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Bhat et al (2012) Tubers are made into a paste and then applied to the joint to cure pain Kambe et al (2014) Tubers are made in various forms (paste and boiled) and then applied to the skin to cure various diseases etc. breast tumors, itching, and physical injuries Similar prospects were also acknowledged by Yuzammi (2018), who documented some Araceae in Bogor Botanic Gardens, Indonesia, for example, Alocasia, Aglaodorum, Aglaonema, etc. Mutaqin et al (2018) Meanwhile, the dominant species of the site, X. sagittifolium, is consumed as an additional food due to its palatable tuber.…”
Section: Remusatia Viviparasupporting
confidence: 65%
See 1 more Smart Citation
“…Bhat et al (2012) Tubers are made into a paste and then applied to the joint to cure pain Kambe et al (2014) Tubers are made in various forms (paste and boiled) and then applied to the skin to cure various diseases etc. breast tumors, itching, and physical injuries Similar prospects were also acknowledged by Yuzammi (2018), who documented some Araceae in Bogor Botanic Gardens, Indonesia, for example, Alocasia, Aglaodorum, Aglaonema, etc. Mutaqin et al (2018) Meanwhile, the dominant species of the site, X. sagittifolium, is consumed as an additional food due to its palatable tuber.…”
Section: Remusatia Viviparasupporting
confidence: 65%
“…This family occupies a wide variety of habitats, including forest understory, river banks, open swamp areas, and even relatively dry areas. Although Araceae is highly diverse in Indonesia, the potential for their collections for conservation and economic purposes has not been fully explored (Yuzammi 2018). Subsequently, Araceae consists of many species that can be used to provide food, medicine, ornaments, and other needs for Indonesians.…”
Section: Introductionmentioning
confidence: 99%
“…Various altitudes will affect air temperature, humidity, rainfall, number of rainy days, oxygen level, light intensity, and soil characteristics (Ohmura 2012;Al-Ahmadi and Al-Ahmadi 2013;Ceballos et al 2021). Suweg has a growing environment with a diverse range (Yuzammi et al 2017). Mukherjee et al (2014) report that the genus Amorphophallus is divided into two groups relating to climatic conditions: the tropical and the sub-tropical.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the tuber and other plant organs of A. paeoniifolius can be used as a source of medicine [2][3][4][5] or a raw food material [6][7][8][9][10][11][12]. Besides having a high potential utilization as both a medicine and food, the productivity of this crop is relatively high at approximately 50-80 ton ha −1 [13].…”
Section: Introductionmentioning
confidence: 99%